Trade as a Wage Disciplining Device - Damiaan Persyn (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
We estimate how trade openness affects the relationship between wages, labour productivity and foreign wages using sector-level time series for several EU member states. In some countries wages became less responsive to foreign wages as trade costs declined. We show this counter-intuitive result is as expected when wages are set by a monopoly union with a preference for wages relative to employment. Trade liberalisation then leads to more wage discipline by forcing unions to set wages more in line with labour productivity. Foreign wages simultaneously become less relevant. Our results call to rethink how trade liberalisation is affecting unionised labour markets, and offer a possible explanation for the mixed evidence found by some tests for international factor price convergence.
Keywords: J50; J31; F16; 330; Unions; globalisation; economic geography; factor price equalisation; Außenhandelsliberalisierung; Lohnpolitik; Lohnniveau; Arbeitsproduktivität; Faktorpreisausgleich; Gewerkschaftsmitgliedschaft; Globalisierung; Transaktionskosten; EU-Staaten